ANALISIS PENGARUH KEBIJAKAN LOAN TO VALUE, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO DAN SUKU BUNGA KREDIT TERHADAP SUPPLY KREDIT KEPEMILIKAN RUMAH PADA BANK TABUNGAN NEGARA. - Nadi, Luh; Wenten, I Ketut (Program Studi Akuntansi FPEB UPI, 2021)
The purpose of this study was conducted to examine and analyze the effect of the variable Loan to Value, Non Performing Loan, Loan to Deposit Ratio and Credit Interest Rate on the KPR Supply at Bank Tabungan Negara Tbk. The research data is obtained from data from the quarterly Financial Reports for the period 2004â€“2018 which are published through the Indonesian Banking Directory which is recorded at the Financial Services Authority (OJK) and the company profile of Bank Tabungan Negara Tbk.Researchers used multiple linear regression in the analysis technique, in which the least squares equation was used and hypothesis testing with t-statistics and F-statistics using a significance level of 5%. The classical assumption test is carried out first, namely the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Based on the results of the t test analysis shows that partially the LTV, NPL and SBK variables have a significant and significant influence on the dependent variable of KPR Supply, while the LDR variable has no and insignificant effect on the dependent variable (KPR Supply) with a probability level of less than 5%. Furthermore, the results of the F test or the simultaneously of Â the LTV, NPL, LDR and SBK variables have a significant effect on KPR supply.